Pengaruh current ratio, debt to equity ratio dan return on asset terhadap financial distress pada Perusahaan Tekstil dan Garmen yang terdaftar di BEI - Putri Ray, Stefany; Listyowati, Listyowati; Setiyorini, Wahyu; Kusumowati, Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This study aims to analyze the effect of Current Ratio, Debt to Equity Ratio and Return On Asset on Financial Distress in textile and garment companies listed on the Indonesia Stock Exchange (IDX). The research period used is 2019-2023. This quantitative study has 20 research population companies, with a sample in this study as many as 9 companies that use the purposive sampling technique as a sampling technique. The data collection method is secondary data obtained from the official website of the Indonesia Stock Exchange. The data analysis methods used were descriptive statistical tests, classical assumption tests (data normality tests, autocorrelation tests, heterokedasticity tests, multicollinearity tests), multiple regression analysis tests, and model accuracy tests (F test), determination coefficient tests (R2), hypothesis tests (t tests), which were processed using the Statistical Product and Service Solutions (SPSS 25) program. The results of the study with a Hypothesis Test (t-Test) seen from the last 5 years, show that the current ratio has a positive and significant effect on financial distress, the debt to equity ratio has no significant effect on financial distress, and the return on asset has a significant effect on financial distress.